Risk and impact of herpes zoster on patients with diabetes: A population-based study, 2009-2014 - Cintia Muñoz-Quiles; Mónica López-Lacort; F. Javier Ampudia-Blasco; Javier Díez-Domingo (Taylor & Francis Group, 2017)
Aims: This study was designed to assess the impact of diabetes on the risk and severity of herpes zoster (HZ), and the impact of HZ on diabetes. It focused primarily on immunocompetent patients aged ≥ 50 years who would be eligible for preventive vaccination. Methods: Using population and healthcare databases of Valencia Region (Spain), a retrospective cohort of all subjects ≥ 50 years was followed up between 2009 and 2014. HZ and diabetes were defined using ICD-9 codes. We compared the incidence of HZ between non-diabetes and diabetes groups and healthcare resource consumption due to HZ in the 6 months following HZ diagnosis using different statistical generalized linear models (GLM). We also compared resources consumption due to diabetes treatment and haemoglobinA1c(HbA1c) levels before and after HZ. Results: The cohort consisted of 2,289,485 individuals ≥ 50 years old, 397,940 of whom had diabetes. HZ incidence rate was 9.3 cases/1000 persons with diabetes-year (95% CI: 9.1-9.4). Incidence increased with age in all groups. The risk of HZ increased in the diabetes group compared to the non-diabetes group (RR 1.2, 95% credibility interval [CrI] 1.17-1.22). Patients with diabetes utilized more health care resources due to their HZ episodes than patients without diabetes. In 24% of well controlled patients with diabetes (HbA1C levels ≤ 6.5%), HbA1C increased after HZ. Conclusions: Diabetes increased by 20% the risk of HZ. HZ contributed to the deterioration of glycaemic control and higher healthcare resource consumption in people with diabetes, becoming a priority population for HZ immunization.